2013
DOI: 10.1136/bmjopen-2013-002916
|View full text |Cite
|
Sign up to set email alerts
|

Changes in smoking behaviours following a smokefree legislation in parks and on beaches: an observational study

Abstract: ObjectiveTo examine the effect of an outdoor smokefree law in parks and on beaches on observed smoking in selected venues.MethodsThe study involved repeated observations in selected parks and beaches in Vancouver, British Columbia, Canada. The main outcome measure was changes in observed smoking rates in selected venues from prelaw to 12 months postlaw.ResultsNo venue was 100% smokefree at the 12-month postlaw observation time point. There was a significant decrease in observed smoking rates in all venues from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
6
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 13 publications
2
6
0
Order By: Relevance
“…Taken together with previous studies,6 7 these results show that smoke-free air laws in outdoor public spaces can be effective and durable. Such policies could offer jurisdictions a simple strategy for reducing exposure to tobacco pollutants (ie, smoke and litter) in outdoor areas.…”
Section: Discussionsupporting
confidence: 86%
“…Taken together with previous studies,6 7 these results show that smoke-free air laws in outdoor public spaces can be effective and durable. Such policies could offer jurisdictions a simple strategy for reducing exposure to tobacco pollutants (ie, smoke and litter) in outdoor areas.…”
Section: Discussionsupporting
confidence: 86%
“…Okoli et al , in their study in Canada, studied the effect of an outdoor smoke-free law in parks and on beaches and reported that there was a significant decrease in observed smoking rates in all venues from prelaw to 12 months post law. 13 Chapman et al estimate the contribution of smoke-free workplaces to the declines in cigarette consumption in Australia and the USA. They reported that smoke-free workplaces are currently responsible for an annual reduction of 602 million cigarettes.…”
Section: Introductionmentioning
confidence: 99%
“…While there has been some published observation of the prevalence of smoking in outdoor areas such as parks, streets, hospital grounds, stadia, near public doorways and on university campuses in North America, England and Australasia (Jancey et al, 2014;Okoli, Johnson, Pederson, Adkins, & Rice, 2013;Thomson, Russell, Jenkin, Patel, & Wilson, 2013), there have been only two studies of the smoking prevalence outside bars/cafés, both in Australia. One study, of a 'purposive sample of 20 pubs and bars within a 7-km radius of the centre' of Melbourne, involving observations on Friday and Saturdays during 7-12 pm, recorded a smoking prevalence of 6.2% and 7.3% before and after the introduction of smokefree indoor policies in 2007 (Brennan et al, 2010).…”
Section: Introductionmentioning
confidence: 99%